Chemical modification of banana starch by the in situ polymerization of ϵ-caprolactone in one step - Ramírez Hernández, Aurelio; Aparicio Saguilan, Alejandro; Mata-Mata, José L.; González-García, Gerardo; Hernández-Mendoza, Héctor; Gutiérrez-Fuentes, Alfredo; Báez-García, Eduardo (Starch - Stärke, 2017)
The chemical modification of starch from physiologically immature bananas (Musa paradisiaca L.) was performed via the in situ polymerization of ϵ-caprolactone (CL) utilizing ammonium decamolybdate as a catalyst to obtain a starch-g-PCL copolymer in one step. The copolymerization conditions were studied by varying the CL/catalyst mass ratio, the reaction temperature, and the reaction time. The final product was characterized using different technical instruments to demonstrate copolymerization. Based on the results, the graft copolymer was successfully synthesized, and the mass yield reached 85.2% at a temperature of 110°C with a DPn(NMR) of 10 and a Mn(NMR) of 1141 Da. The monomer conversion to copolymer followed a power-law model with a reaction order of 3/2. The thermal properties and crystallinity of the starch and polycaprolactone in the copolymer were affected due to the formation of starch-g-PCL clusters.
Keywords: Almidón de plátano; Modificación química